Analysis Of Local Coffee Shop Communication Strategy From The Perspective Of Communication Sociology In The Case Of Teulu Coffee Bintaro - Azzahra Siti Kamila Imran; Muhammad Husein Ghozali; Jessica M. Szczuka; Olawale Ajai (LPPM Universitas PGRI Sumatera Barat, 2024)
Engaging with the surrounding community by building engagement with the surrounding community is an important strategy for coffee shops. This can be in the form of collaborating with community events, local sponsorships, or even becoming a meeting place for local groups. The purpose of this study is to observe the communication strategy of Teulu coffee shop from the perspective of communication sociology in increasing brand awareness on social media. This type of research is qualitative. Qualitative research methods can be obtained from secondary data, namely various sources, such as social theory, relevant previous research, and research in the field studied by the researcher. The data analysis technique used is qualitative data analysis techniques. The results of the study stated that Teulu Coffee succeeded in implementing an effective marketing communication sociology strategy by utilizing social media, especially Instagram, and location-based advertising. They succeeded in creating interesting content and actively interacting with customers through these platforms. The conclusion of this study is that Teulu Coffee also succeeded in differentiating or specializing from competitors by focusing on superior product quality, a comfortable place concept, and unique coffee variations. Implications In terms of segmentation and targeting, Teulu Coffee has taken a detailed approach by utilizing consumer data and market analysis to reach the right audience with the right message.